Railroads and Weather From Fogs to Floods and Heat to Hurricanes, the Impacts of Weather and Climate on American Railroading - Changnon, Stanley (American Meteorological Society : Imprint: American Meteorological Society, 2006)
This award-winning "must-read" for weather and railroad buffs is the first book to cover the impacts of major storms of the last hundred years on this massive American industry. Includes 210 historic and color train photos and special Katrina coverage.